Environmental context of the Caune de l'Arago Acheulean occupations (Tautavel, France), new insights from microvertebrates in Q–R levels. (8th August 2016) - Lebreton, Loïc; Desclaux, Emmanuel; Hanquet, Constance; Moigne, Anne-Marie; Perrenoud, Christian
Abstract: The comparison between the microvertebrates from the Caune de l'Arago Q–R levels and P levels highlighted differences in their faunal palaeocommunities, notably with the presence of Pliomys episcopalis in the former level. The taphonomic analyses of birds, lagomorphs and micromammals remains have shown that these microvertebrate accumulations are due to the coprocoenosis of nocturnal birds of prey. Bubo bubo seems to be the main accumulating agent. The faunal representation biases are minimal between these levels. The changes observed in the faunal composition of the different levels rather reflect environmental changes than a predation bias. The environment present during the deposition of Q–R levels appears to be temperate with wooded features, which differentiates it from the rest of the Ensemble I. These differences could correspond to an interstadial period during Marine Isotopic Stage (MIS) 14 or to a transitional phase with the isotopic stage 15.